Uji Viabilitas dan Pertumbuhan Kecambah Kacang Hijau (Vigna Radiata) Selama 11 Hari - Na’illah Ega Sivana; Nathania Rahadatul ‘Aisy; Nurul Mawaddah; Rahajeng Galuh Tribuana; Rifqi Ilham; Ita Fitriyyah (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
This study aims to test the viability and growth of mung bean (Vigna radiata) sprouts for 11 days. Mung beans were chosen as the object of research because of the ease of the germination process and high nutritional value. The methods used include preparing germination media with moistened opaque paper, as well as observing the parameters of normal, abnormal, and dead seeds. The results showed that in the first repetition, the number of normal sprouts reached 17 seeds with a germination power of 68%, while in the second repetition there were only 11 normal seeds. This study indicates that environmental conditions and proper treatment greatly affect seed viability. Thus, it is important to maintain optimal conditions to increase germination and plant growth results.